2015
DOI: 10.1016/j.reprotox.2015.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to di-(2-ethylhexyl) phthalate (DEHP) affects reproductive outcomes in female mice

Abstract: This study tested the hypothesis that prenatal DEHP exposure affects female reproduction. To test this hypothesis, pregnant female CD-1 mice were orally dosed daily with tocopherol-stripped corn oil (vehicle control) or DEHP (20μg/kg/day-750mg/kg/day) from gestation day 11-birth. Pups were counted, weighed, and sexed at birth, ovaries were subjected to evaluations of follicle numbers on postnatal days (PNDs) 8 and 21, and fertility was evaluated at 3-9 months. The results indicate that prenatal DEHP exposure i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
4
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 44 publications
5
48
4
2
Order By: Relevance
“…For example, early rodent studies found that DEHP exposure was associated with decreased fetal and birth weight (31, 32]), while similar recent studies are consistent with our findings of no association (33, 34). Animal studies of in utero DBP exposure have also observed inconsistent effects on birth weight, with several studies reporting no effect (35-38), while others reported either decreased (39-41) or increased (42) birth weight.…”
Section: Discussionsupporting
confidence: 92%
“…For example, early rodent studies found that DEHP exposure was associated with decreased fetal and birth weight (31, 32]), while similar recent studies are consistent with our findings of no association (33, 34). Animal studies of in utero DBP exposure have also observed inconsistent effects on birth weight, with several studies reporting no effect (35-38), while others reported either decreased (39-41) or increased (42) birth weight.…”
Section: Discussionsupporting
confidence: 92%
“…Reproductive outcome of F0 dams treated with DEHP from gestational day 1 to 19. Previous studies have reported that DEHP is able to induce a dose-dependent decrease in mouse fertility (23), and affect reproductive outcomes in female mice (24). In the present study, no significant decline in fertility was exhibited by F0 dams treated with 0.05 mg/kg DEHP; however, the abortion rate was 100% in the 500 mg/kg DEHP dose group compared with 0% in the control and 0.05 mg/kg DEHP groups.…”
Section: Discussioncontrasting
confidence: 63%
“…This is the first time this phthalate mixture has been tested in vivo . Thus, doses of phthalate mixture were chosen to cover a wide environmentally relevant range and to include some of the doses of individual phthalates that have been shown to adversely affect reproductive health during prenatal exposure [1719, 23]. The estimated general population daily exposure level of DEHP is 3–30 μg/kg/day [24].…”
Section: Methodsmentioning
confidence: 99%
“…We also included two high doses of mixture (200 and 500 mg/kg/day, which contain approximately 40 and 100 mg/kg/day of DEHP, respectively) to test the effects of this mixture at a level higher than human expose range and to compare our results with available information from single phthalate studies that used doses close to this level. Previous studies have shown that gestational exposure to DEHP decreased the thickness of thecal cell layers at 50 and 300 mg/kg/day [23], disrupted steroidogenic enzyme gene expression and increased estradiol levels at 100 mg/kg/day [19], increased preantral follicle numbers at 200 μg/kg/day and 500 mg/kg/day [17], increased ovarian weights at 0.05 and 5 mg/kg/day [18], and induced breeding complications at 200 μg/kg/day and 750 mg/kg/day [17]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation